Analysis Of Vibration Signals And Surface Characteristics Of Cylindrical Roller Bearing - Ahmad, Andree (2014)
This work aims to establish the relation between the vibration level and the surface roughness of the bearing running under lightly oiled, greased and dry conditions. Kajian ini dijalankan untuk mengesahkan kaitan antara paras getaran dan kekasaran permukaan galas yang dijalankan pada keadaan minyak yang nipis, pelinciran gris dan kering.